NIPAL1 as a prognostic biomarker associated with pancreatic adenocarcinoma progression and immune infiltration - Youlong Zhu; Zongze Qi; Shaoqi Zu; Fangchao Yang; Yanming Wang; Lei Zhu; Xintong Li; Ruixue Li; Hong Zhu (BMC Cancer)
Abstract Pancreatic adenocarcinoma (PAAD) is a highly malignant tumor in the digestive system, with an increasing incidence and mortality rate globally. Recent genetic studies have revealed that the abnormal expression and functional dysregulation of various genes are involved in the occurrence and progression of pancreatic cancer. NIPA-like proteins (NIPAs) are expressed in a variety of cancer types, yet the role of NIPAL1 in cancer remains unclear. Therefore, further research is required to determine its diagnostic significance and understand its biological functions in cancer. Primitive RNA sequencing (RNA-seq) data of PAAD from The Cancer Genome Atlas (TCGA) was utilized for bioinformatics analysis to characterize the expression levels of NIPAL1 in tumor and normal tissues. Differentially expressed genes (DEGs) were identified, and Gene Set Enrichment Analysis (GSEA) was performed to elucidate potential biological mechanisms of NIPAL1 involved in PAAD development. Additionally, we analyzed the correlation between NIPAL1 expression, immune cell infiltration, and PAAD progression. The Genomics of Drug Sensitivity in Cancer (GDSC) database was utilized to investigate the relationship between NIPAL1 expression and the efficacy of common drugs used in chemotherapy and targeted therapy in patients with pancreatic cancer. Subsequently, we predicted five small-molecule drugs targeted at NIPAL1 using molecular docking. Finally, high expression of NIPAL1 in tumor tissues was validated through immunohistochemistry. In pancreatic cancer cell lines, changes in phenotypes such as proliferation, migration, and invasion following the knockdown of NIPAL1 were assessed. Finally, we established a subcutaneous tumor-bearing mouse model to further validate its therapeutic significance in vivo.